Marine natural products as inhibitors of cystathionine beta-synthase activity. Issue 5 (1st March 2015) - Thorson, Megan K.; Van Wagoner, Ryan M.; Harper, Mary Kay; Ireland, Chris M.; Majtan, Tomas; Kraus, Jan P.; Barrios, Amy M.
Graphical abstract: Abstract: A library consisting of characterized marine natural products as well as synthetic derivatives was screened for compounds capable of inhibiting the production of hydrogen sulfide (H2 S) by cystathionine beta-synthase (CBS). Eight hits were validated and shown to inhibit CBS activity with IC50 values ranging from 83 to 187 μM. The majority of hits came from a series of synthetic polyandrocarpamine derivatives. In addition, a modified fluorogenic probe for H2 S detection with improved solubility in aqueous solutions is reported.